The Effect of Duolingo Application in Improving Students' English Skills: A Research of Grade X Students at SMKN 3 Baubau - Fitriani Fitriani; Gia Puspita Mokodompit (JELITA, 2025)
This study investigated the impact of Duolingo application on English language proficiency among Grade XI students at SMKN 3 Baubau, Southeast Sulawesi. The integration of technology in English language learning presents new opportunities for Indonesian vocational schools, yet research on mobile learning application effectiveness in this specific context remains limited. This qualitative research at SMKN 3 Baubau, Southeast Sulawesi, used Duolingo as a learning medium, showing positive impacts on students' English skills (speaking, writing, reading, listening). Data from observations, tests, and interviews revealed that Duolingo increased motivation, vocabulary, grammar comprehension, text understanding, and pronunciation. Its interactive, gamified features reduced monotony and boosted enthusiasm, aligning with research highlighting the benefits of technology and gamification in language learning. Duolingo proves effective for enjoyable and efficient English learning.